The effect of motivation and barrier towards reading habits : a case study among parents in UiTM Kelantan / Elida Nurul Wafa Hamzah, Noor Amalina Murad, Nor Amelia Mohd Noor Arif - Hamzah, Elida Nurul Wafa; Murad, Noor Amalina; Mohd Noor Arif, Nor Amelia (2018)
Nowadays, Malaysian do not make reading as their culture. This is because Malaysian was not educated since their childhood to love reading. Thus, a research was conducted to measure the reading habits between parents in UiTM Kelantan. The aim for this research is to study effect of motivation and barrier towards reading habits among parents in UiTM Kelantan. There are 174 respondents which are staff in UiTM Kelantan. They were selected by using systematic sampling technique. This Structural Equation Modelling apply the second approach which is Partial Least Squares (PLS-SEM) that analyzed by using SmartPLS and IBM SPSS Software. The findings show that extrinsic motivation has an effect towards reading habits and socio-economic is one of the barriers that give an effect to reading habits. Next, extrinsic motivation is mediate between time and reading habits. As the conclusion, parents play important role in order to increase the reading habits among children since parents are the first teacher to their children. Children also are influenced by their parents as they learning by example easily